Positive pole piece, preparation method thereof and battery
By introducing fluorine groups into the binder of the positive electrode sheet, the hydrophobicity of the positive electrode material is solved, and the cycle life and kinetic performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411670058.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-11
AI Technical Summary
Due to the small particle size and large specific surface area of lithium manganese iron phosphate, the electrode sheet is prone to absorb water, affecting the cycle life of the battery.
The first bonding material with hydrophobic groups is used as the binder for the positive electrode active material layer. By introducing fluorine groups on the surface of the bonding material, the surface hydrophobicity of the binder is improved, thereby improving the hydrophobic properties of the positive electrode sheet.
It significantly improves the hydrophobic performance of the positive electrode sheet, extends the cycle life of the battery, reduces the internal resistance of the battery, and improves the dynamic performance.
Smart Images

Figure CN119601581A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode sheet and a preparation method thereof, and a battery. Background Art
[0002] In recent years, with the vigorous development of the new energy industry, especially the development of electric vehicles, the power battery industry has developed rapidly. At present, the mainstream power batteries on the market are mainly divided into two chemical systems: lithium iron phosphate and ternary nickel-cobalt-manganese materials. With the continuous development of the positive electrode material industry, lithium iron manganese phosphate is increasingly favored by power battery manufacturers and host manufacturers due to its high specific energy characteristics and the same safety as lithium iron phosphate. However, the particle size of lithium iron manganese phosphate material is small and the specific surface area is large, which makes the pole piece easy to absorb water, affecting the cycle life of the battery. Summary of the invention
[0003] The embodiments of the present invention provide a positive electrode plate and a preparation method thereof and a battery, which can effectively improve the cycle life of the battery.
[0004] In order to achieve the above-mentioned object, according to a first aspect of the present application, there is provided a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer comprises at least one coating layer;
[0005] The coating comprises a binder, wherein the binder comprises a first binder material and / or a second binder material;
[0006] Wherein, at least one of the coatings includes the first bonding material, and the first bonding material has a hydrophobic group.
[0007] In some embodiments, the positive electrode active material layer includes a first coating layer and a second coating layer, the first coating layer is located on a side of the second coating layer away from the positive electrode current collector, the first coating layer includes the first binding material, and the second coating layer includes the first binding material or the second binding material.
[0008] In some embodiments, the hydrophobic group comprises fluorine.
[0009] In some embodiments, the first bonding material is polyvinylidene fluoride having a hydrophobic group, and the second bonding material is polyvinylidene fluoride.
[0010] In some embodiments, in the first bonding material, the hydrophobic group is a fluorine-containing group, and the fluorine-containing group is connected to the polyvinylidene fluoride through a chemical bond.
[0011] In some embodiments, the coating further comprises a pore former; the binder content in the first coating is less than or equal to the binder content in the second coating, and the pore former content in the first coating is less than or equal to the pore former content in the second coating.
[0012] In some embodiments, the coating further comprises a positive electrode active material, a conductive agent, and a dispersant;
[0013] The total mass ratio of the positive electrode active material, the conductive agent, the binder, the dispersant and the pore former in the positive electrode active material layer is a:b:c:d:e, wherein a+b+c+d+e=1;
[0014] The mass ratio of the positive electrode active material, the conductive agent, the binder, the dispersant and the pore former in the first coating layer is (1-bc-0.6d-0.5e): b:c:0.6d:0.5e;
[0015] The mass ratio of the positive electrode active material, the conductive agent, the binder, the dispersant and the pore former in the second coating layer is (1-bc-1.4d-1.5e): b:c:1.4d:1.5e.
[0016] In some embodiments, the positive electrode active material includes lithium manganese iron phosphate.
[0017] In some embodiments, the dispersant is a non-ionic dispersant.
[0018] In some embodiments, in the positive electrode active material layer, the mass percentage of the positive electrode active material ranges from 95.5% to 97.5%, the mass percentage of the conductive agent ranges from 0.3% to 1.6%, the mass percentage of the binder ranges from 1.4% to 2.0%, the mass percentage of the dispersant ranges from 0.1% to 0.4%, and the mass percentage of the pore former ranges from 0.1% to 1.0%.
[0019] According to a second aspect of the present application, a method for preparing a positive electrode sheet is provided, comprising:
[0020] Mixing the positive electrode active material, the conductive agent, the dispersant and the pore-forming agent with a solvent to form a first mixed solution;
[0021] Mixing a first bonding material with the first mixed liquid to form a second mixed liquid;
[0022] Using the second mixed solution to form at least one coating on the positive electrode current collector to obtain a positive electrode sheet;
[0023] Wherein, the first bonding material has a hydrophobic group.
[0024] In some embodiments, the step of preparing the first bonding material comprises:
[0025] The precursor of the first bonding material is subjected to plasma treatment using a fluorine-containing gas to obtain the first bonding material having a fluorine-containing group.
[0026] In some embodiments, before the step of plasma-treating the precursor of the first bonding material with a fluorine-containing gas, the method further comprises:
[0027] The precursor of the first bonding material is plasma treated with oxygen.
[0028] In some embodiments, the step of forming at least one coating layer on the positive electrode current collector using the second mixed solution comprises:
[0029] Applying the second mixed solution onto the positive electrode current collector to form a second coating layer;
[0030] The second mixed solution is applied to a side of the second coating layer away from the positive electrode current collector to form a first coating layer.
[0031] In some embodiments, the step of forming at least one coating layer on the positive electrode current collector using the second mixed solution comprises:
[0032] Mixing a second bonding material with the first mixed solution to form a third mixed solution;
[0033] Applying the third mixed solution onto the positive electrode current collector to form a second coating layer;
[0034] The second mixed solution is applied to a side of the second coating layer away from the positive electrode current collector to form a first coating layer.
[0035] According to a third aspect of the present application, a battery is provided, comprising the positive electrode plate as described in the first aspect.
[0036] The present application provides a positive electrode plate, a preparation method thereof, and a battery. The active material coating of the positive electrode plate of the present application adopts a first binding material having a hydrophobic group as a binding agent, which can significantly improve the surface hydrophobicity of the binding agent. The improvement of the surface hydrophobicity of the binding agent is beneficial to the improvement of the overall hydrophobicity of the active material coating, and then can improve the hydrophobicity of the positive electrode plate, thereby effectively improving the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0038] Figure 1 It is a structural schematic diagram of a positive electrode sheet provided in an embodiment of the present application;
[0039] Figure 2 It is a schematic diagram of the structure of another positive electrode sheet provided in an embodiment of the present application;
[0040] Figure 3 It is a flow chart of a method for preparing a positive electrode sheet provided in an embodiment of the present application. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0042] This application provides a positive electrode plate, please refer to Figure 1-Figure 2 The positive electrode sheet includes a positive electrode current collector 10 and a positive electrode active material layer 20 arranged on the positive electrode current collector 10; the positive electrode active material layer 20 includes at least one coating layer, the coating layer includes a binder, and the binder includes a first binder material and / or a second binder material; wherein, at least one coating layer includes a first binder material, and the first binder material has a hydrophobic group.
[0043] The first bonding material may be obtained by surface-modifying the precursor of the first bonding material, and hydrophobic groups are introduced into the surface of the precursor of the first bonding material to make it hydrophobic. The precursor of the first bonding material may be the same as the second bonding material, but is not limited thereto.
[0044] Specifically, the first bonding material may be polyvinylidene fluoride having a hydrophobic group, a precursor of the first bonding material may be polyvinylidene fluoride (PVDF), and the second bonding material may be polyvinylidene fluoride (PVDF), but is not limited thereto.
[0045] In some embodiments, please refer to Figure 2 The positive electrode active material layer 20 may include a coating layer, that is, the positive electrode plate may form the positive electrode active material layer 20 on the surface of the positive electrode current collector 10 using a single-layer coating process. When the positive electrode plate includes a coating layer, the binder in the coating layer includes a first binder material.
[0046] In some embodiments, please refer to Figure 1, the positive electrode active material layer 20 may include two layers of stacked coatings, that is, the positive electrode plate may adopt a double-layer coating process to form the positive electrode active material layer 20 on the surface of the positive electrode collector 10. When the positive electrode plate includes two coatings, the binder in at least one coating layer on the surface (that is, the coating layer away from the positive electrode collector 10) includes the first binding material.
[0047] In one embodiment, please refer to Figure 1 The positive electrode active material layer 20 may include a first coating layer 21 and a second coating layer 22, wherein the first coating layer 21 is located on a side of the second coating layer 22 away from the positive electrode current collector 10, wherein the binder in the first coating layer 21 includes a first binding material, and the binder in the second coating layer 22 includes a second binding material.
[0048] In one embodiment, please refer to Figure 1 The positive electrode active material layer 20 may include a first coating layer 21 and a second coating layer 22, wherein the first coating layer 21 is located on a side of the second coating layer 22 away from the positive electrode current collector 10, wherein the binder in the first coating layer 21 includes a first binding material, and the binder in the second coating layer 22 includes a first binding material.
[0049] In the above-mentioned embodiment of the present application, the positive electrode active material layer includes a first binding material having a hydrophobic group. Since the hydrophobic group is introduced on the surface of the binding material, the surface hydrophobicity of the binding agent can be significantly improved, and the improvement of the surface hydrophobicity of the binding agent is conducive to improving the overall hydrophobicity of the active material coating, and then can effectively improve the hydrophobicity of the positive electrode plate to improve the cycle life of the battery. Therefore, the positive electrode plate of the present application using the first binding material having a hydrophobic group can effectively improve the problem of the prior art that the plate is easy to absorb water and affect the battery life.
[0050] In some embodiments, the hydrophobic group includes fluorine (F). For example, a fluorine group can be introduced into the surface of the bonding material. The fluorine group has a low surface energy property and can significantly reduce the surface energy of the bonding material and improve the hydrophobicity of the bonding material surface.
[0051] In addition, the high endurance requirements of new energy vehicles force higher and higher requirements on battery energy density. The thick electrode design is conducive to improving the energy density of the battery, but the thick electrode has the problem of poor dynamic performance, resulting in poor battery rate performance. For the thick lithium manganese iron phosphate electrode, it not only has the problem of easy water absorption of the electrode piece affecting the cycle life, but also has the problem of poor dynamic performance.
[0052] This application introduces fluorine groups to the surface of the adhesive material, which can not only improve the surface hydrophobicity of the adhesive, improve the cycle life of the battery, but also reduce the internal resistance of the battery and improve the battery dynamics. Among them, since a large number of fluorine groups are introduced to the surface of the first adhesive material, the introduction of fluorine groups improves the electron affinity of the surface of the first adhesive material, and distributes them in the material of the positive electrode active material layer to reduce the impedance of electron transfer, thereby reducing the internal resistance of the battery, and then can improve the dynamics of the battery. Therefore, when the positive electrode plate of the present application adopts the first adhesive material with a fluorine group, it can not only improve the hydrophobicity of the positive electrode plate, but also reduce the internal resistance of the battery, which can effectively improve the cycle life and dynamics of the battery.
[0053] In some embodiments, the first bonding material having a fluorine group can be obtained by plasma treating a precursor of the first bonding material using a fluorine-containing gas. 4 The precursor of the first bonding material, polyvinylidene fluoride (PVDF), is subjected to plasma treatment by gas to obtain polyvinylidene fluoride (PVDF) with F groups on the surface, wherein the polyvinylidene fluoride (PVDF) with F groups on the surface is the first bonding material. 4 A large number of F groups are introduced into the surface of PVDF after gas plasma treatment, which significantly improves the electron affinity and surface hydrophobicity of PVDF. Therefore, the kinetic performance and cycle life of the positive electrode sheet using PVDF containing F groups on the surface as a binder can be significantly improved.
[0054] In CF 4 During the gas plasma treatment of PVDF, CF 4 The gas forms fluorine-containing plasma under the action of the plasma equipment. The plasma bombards the PVDF surface. Through a series of physical and chemical processes, a large number of F groups are introduced into the PVDF surface. The F groups are connected to the polyvinylidene fluoride through chemical bonds, so that the PVDF surface forms a hydrophobic surface, which can significantly improve the hydrophobic properties of PVDF.
[0055] In some embodiments, before the surface of the precursor of the first bonding material is treated with fluorine-containing gas plasma, oxygen (O 2 ) plasma treating the surface of the precursor of the first bonding material, 2 Plasma treatment can activate the material surface, increase the surface area and adhesion of the material, increase the subsequent attachment rate of F groups on the material surface, and increase the fluorine content, so as to further reduce the internal resistance of the battery and improve the dynamic performance of the battery.
[0056] In the present application, the positive electrode active material layer also includes a positive electrode active material, a conductive agent, a dispersant and a pore-forming agent. The positive electrode active material layer is formed on the surface of the positive electrode current collector after mixing the positive electrode active material, the conductive agent, the binder, the dispersant and the pore-forming agent and then coating, drying, rolling and other processes.
[0057] The positive electrode active material includes lithium manganese iron phosphate, but is not limited thereto.
[0058] The conductive agent may include at least one of conductive carbon black (SP), carbon nanotubes (CNTs), carbon nanofibers, and the like.
[0059] The dispersant is a non-ionic dispersant, including polyethylene glycol octylphenyl ether (TritonX-100), polyoxyethylene ether, etc. The dispersant can inhibit the agglomeration of the positive electrode active material and the conductive agent, thereby making the slurry dispersed evenly. The use of a non-ionic dispersant in this application can further improve the uniformity of the positive electrode slurry and improve the electrochemical performance of the positive electrode sheet.
[0060] Pore formers include, but are not limited to, oxalic acid or citric acid.
[0061] In the positive electrode active material layer, the mass percentage of the positive electrode active material ranges from 95.5% to 97.5%, the mass percentage of the conductive agent ranges from 0.3% to 1.6%, the mass percentage of the binder ranges from 1.4% to 2.0%, the mass percentage of the dispersant ranges from 0.1% to 0.4%, and the mass percentage of the pore former ranges from 0.1% to 1.0%.
[0062] In one embodiment, the positive electrode active material layer includes: lithium manganese iron phosphate, conductive carbon black (SP), carbon nanotubes (CNT), polyvinylidene fluoride (PVDF), polyethylene glycol octyl phenyl ether and a pore-forming agent. Among them, the mass percentage of lithium manganese iron phosphate ranges from 95.5% to 97.5%, the mass percentage of conductive carbon black ranges from 0.2% to 1.0%, the mass percentage of carbon nanotubes ranges from 0.1% to 0.6%, the mass percentage of polyvinylidene fluoride with fluorine groups ranges from 1.4% to 2.0%, the mass percentage of polyethylene glycol octyl phenyl ether ranges from 0.1% to 0.4%, and the mass percentage of the pore-forming agent ranges from 0.1% to 1.0%. Among them, the pore-forming agent is oxalic acid or citric acid, and the polyvinylidene fluoride with fluorine groups refers to CF 4 Polyvinylidene fluoride after gas plasma treatment.
[0063] In some embodiments, the binder content in the first coating layer is less than or equal to the binder content in the second coating layer, and the pore former content in the first coating layer is less than or equal to the pore former content in the second coating layer.
[0064] Furthermore, the binder content in the second coating layer can be 1.5 to 2.5 times the binder content in the first coating layer, and the pore former content in the second coating layer can be 2.5 to 3.5 times the pore former content in the first coating layer. When the binder content and the pore former content in the first coating layer and the second coating layer are within the above range, the positive electrode sheet can have a better porosity and better uniformity of void distribution, which can improve the rate performance of the thick electrode.
[0065] The present application uses layered coating and adds different proportions of binder and pore former in the first coating and the second coating, so that the prepared positive electrode sheet has a high porosity and uniform void distribution, which can effectively improve the rate performance of the thick electrode. Since the binder and pore former particles in the coating will migrate to the surface of the coating during the drying and rolling processes of the positive electrode active material layer, the binder and pore former in the final positive electrode sheet are unevenly distributed, and the void distribution is uneven, which affects the dynamic performance of the battery. The present application makes the binder and pore former content in the second coating close to the positive electrode current collector greater than the binder and pore former content in the first coating, so as to balance the migration of the binder and pore former particles in the second coating to the first coating in the subsequent drying, rolling and other processes, thereby making the final positive electrode sheet have a high porosity and uniform void distribution, so as to improve the rate performance of the thick electrode.
[0066] In some embodiments, the total mass ratio of each component of the positive electrode active material, the conductive agent, the binder, the dispersant and the pore former in the positive electrode active material layer is a:b:c:d:e, wherein a+b+c+d+e=1; the mass ratio of the positive electrode active material, the conductive agent, the binder, the dispersant and the pore former in the first coating layer is (1-bc-0.6d-0.5e):b:c:0.6d:0.5e; the mass ratio of the positive electrode active material, the conductive agent, the binder, the dispersant and the pore former in the second coating layer is (1-bc-1.4d-1.5e):b:c:1.4d:1.5e. When the positive electrode active material, the conductive agent, the binder, the dispersant and the pore former in the first coating layer and the second coating layer have the above ratio, the battery has better energy density, rate performance and cycle life.
[0067] In one embodiment, the positive electrode active material is lithium manganese iron phosphate, the conductive agent is conductive carbon black (SP) and carbon nanotubes (CNT), the binder is polyvinylidene fluoride (PVDF) having a fluorine group, the dispersant is polyethylene glycol octylphenyl ether, and the pore-forming agent is oxalic acid or citric acid.
[0068] Specifically, the total mass ratio of the components in the positive electrode active material layer is lithium manganese iron phosphate: conductive carbon black: carbon nanotubes: polyvinylidene fluoride having fluorine groups: polyethylene glycol octylphenyl ether: pore-forming agent = a:b 1 :b 2:c:d:e, where a+b 1 +b 2 +c+d+e=1. The mass ratio of the components in the first coating is lithium iron manganese phosphate: conductive carbon black: carbon nanotubes: polyvinylidene fluoride with fluorine groups: polyethylene glycol octylphenyl ether: pore former = (1-bc-0.6d-0.5e): b 1 :b 2 : c: 0.6d: 0.5e; the mass ratio of each component in the second coating is lithium manganese iron phosphate: conductive carbon black: carbon nanotubes: polyvinylidene fluoride with fluorine groups: polyethylene glycol octylphenyl ether: pore-forming agent = (1-bc-1.4d-1.5e): b 1 :b 2 :c:1.4d:1.5e.
[0069] The present application also provides a method for preparing a positive electrode sheet to prepare the positive electrode sheet as described above.
[0070] In some embodiments, when the positive electrode sheet adopts a single-layer coating process, the method for preparing the positive electrode sheet includes the steps of:
[0071] S1, mixing the positive electrode active material, the conductive agent, the dispersant and the pore-forming agent with a solvent to form a first mixed solution;
[0072] S2, mixing the first bonding material with the first mixed solution to form a second mixed solution, wherein the first bonding material has a hydrophobic group;
[0073] S3. Using the second mixed solution, form at least one coating on at least one surface of the positive electrode current collector to obtain a positive electrode sheet.
[0074] In some embodiments, when the positive electrode sheet adopts a double-layer coating process, the preparation method of the positive electrode sheet includes the steps of:
[0075] S1, mixing the positive electrode active material, the conductive agent, the dispersant and the pore-forming agent with a solvent to form a first mixed solution;
[0076] S2, mixing the first bonding material with the first mixed solution to form a second mixed solution, wherein the first bonding material has a hydrophobic group;
[0077] S3, mixing the second bonding material with the first mixed liquid to form a third mixed liquid;
[0078] S4, applying the third mixed solution to at least one surface of the positive electrode current collector to form a second coating;
[0079] S5. Apply the second mixed solution to the side of the second coating layer away from the positive electrode current collector to form a first coating layer, thereby obtaining a positive electrode sheet.
[0080] In this embodiment, the first coating layer uses a first binding material having a hydrophobic group, and the second coating layer uses a second binding material that does not contain a hydrophobic group. Since the first coating layer is located on the surface of the second coating layer, and the first coating layer uses the first binding material having a hydrophobic group as a binder, the surface hydrophobicity of the first coating layer is improved, the second coating layer can be protected, and the problem that the positive electrode sheet easily absorbs water and affects the battery cycle life can be effectively improved.
[0081] In some embodiments, the binder in the first coating layer and the second coating layer may both adopt a first binder material having a hydrophobic group to further improve the hydrophobicity and dynamic performance of the battery.
[0082] Specifically, the method for preparing the positive electrode sheet includes the following steps:
[0083] S1, mixing the positive electrode active material, the conductive agent, the dispersant and the pore-forming agent with a solvent to form a first mixed solution;
[0084] S2, mixing the first bonding material with the first mixed solution to form a second mixed solution, wherein the first bonding material has a hydrophobic group;
[0085] S3, applying the second mixed solution to at least one surface of the positive electrode current collector to form a second coating;
[0086] S4. Apply the second mixed solution to the side of the second coating layer away from the positive electrode current collector to form a first coating layer, thereby obtaining a positive electrode sheet.
[0087] In the above embodiment, the step of preparing the first bonding material includes: using a fluorine-containing gas to perform plasma treatment on a precursor of the first bonding material to obtain a first bonding material having a fluorine-containing group. The fluorine-containing gas may be CF 4 , but not limited to this.
[0088] Furthermore, before the step of performing plasma treatment on the precursor of the first bonding material using the fluorine-containing gas, the method further includes: performing plasma treatment on the precursor of the first bonding material using oxygen to activate the surface of the precursor of the first bonding material.
[0089] In the above preparation method, during the plasma treatment, the power of the plasma is 50W to 100W, and the time is 100s to 500s, preferably 200s to 400s.
[0090] In the above preparation method, the first bonding material may be polyvinylidene fluoride having a hydrophobic group, the precursor of the first bonding material may be polyvinylidene fluoride (PVDF), and the second bonding material may be polyvinylidene fluoride (PVDF).
[0091] The present application also provides a battery, which includes the positive electrode plate as described above.
[0092] Specifically, the battery includes a battery housing and an electrolyte, a negative electrode sheet, a separator and the positive electrode sheet as described above, which are located in the battery housing. The battery housing has a receiving cavity, and the negative electrode sheet, the separator and the positive electrode sheet are stacked in sequence in the receiving cavity, and the electrolyte is contained in the receiving cavity. The material of the battery housing can be metal, such as aluminum, steel, etc.
[0093] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, and the negative electrode active material layer may include graphite, a conductive agent, a binder, etc. The conductive agent may be conductive carbon black, acetylene black, Ketjen black, etc., and the binder may be styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), etc., but is not limited thereto.
[0094] The following is a further description of the positive electrode sheet, preparation method thereof and battery of the present application through specific embodiments.
[0095] 1. Preparation of batteries
[0096] Example 1
[0097] 1. Battery preparation method
[0098] (1) Preparation of positive electrode sheet
[0099] Please refer to Figure 3 , the steps for preparing the positive electrode sheet include:
[0100] S1, mixing the positive electrode active material, the conductive agent, the dispersant and the pore-forming agent with N-methylpyrrolidone (NMP) to form a first mixed solution;
[0101] S2, treating polyvinylidene fluoride (PVDF) with plasma in oxygen to activate the surface of PVDF, and then treating the PVDF with oxygen plasma in CF 4 Plasma treatment is performed in the gas to obtain PVDF having fluorine groups (i.e., the first bonding material);
[0102] S3, adding PVDF having a fluorine group to N-methylpyrrolidone (NMP) and mixing them to form a binder glue solution, and mixing it with the first mixed solution of step S1 to form a second mixed solution (i.e., positive electrode slurry);
[0103] S4, applying the second mixed solution of step S3 to at least one surface of the positive electrode current collector to form a second coating;
[0104] S5, applying the second mixed solution of step S3 to the side of the second coating layer away from the positive electrode current collector to form a first coating layer, and then drying and rolling to obtain a positive electrode sheet.
[0105] Wherein, in step S1, the positive electrode active material is lithium manganese iron phosphate (LMFP), the conductive agent is conductive carbon black (SP) or carbon nanotube (CNT), the dispersant is polyethylene glycol octylphenyl ether, and the pore-forming agent is oxalic acid or citric acid.
[0106] The mass ratio of each component in the first coating is LMFP: SP: CNT: PVDF (containing F group): dispersant: pore-forming agent = 97.62%: 0.5%: 0.4%: 1.08%: 0.2%: 0.2%; the mass ratio of each component in the second coating is LMFP: SP: CNT: PVDF (containing F group): dispersant: pore-forming agent = 95.78%: 0.5%: 0.4%: 2.52%: 0.2%: 0.6%. Among them, PVDF (containing F group) refers to CF 4 PVDF after gas plasma treatment.
[0107] In step S2, the plasma source power is 75 W, the plasma generator frequency is 40 KHz, the gas flow meter is 300 ml / min, and the processing time is 300 s.
[0108] (2) Preparation of negative electrode sheet
[0109] The negative electrode active material, conductive agent and binder are dispersed in a solvent, stirred evenly to obtain a negative electrode slurry, and coated on the negative electrode collector. After drying, rolling and other processes, the negative electrode sheet is obtained.
[0110] The negative electrode active material is graphite (AG), the conductive agent is conductive carbon black (SP), and the binder includes sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The mass ratio of each component in the negative electrode sheet is AG: SP: CMC: SBR = 96.7%: 0.6%: 1.2%: 1.5%.
[0111] (3) Preparation of batteries
[0112] The vacuum-dried positive electrode sheets, separators and negative electrode sheets are assembled and then cut, die-cut, striped and placed in the battery casing. The electrolyte is then injected under high temperature and negative pressure to assemble into a square aluminum shell battery.
[0113] Among them, the diaphragm is a double-sided mixed coating diaphragm of 7+2+2, 7 is the base film thickness, 2 is the mixed coating thickness, and the thickness unit is μm;
[0114] The electrolyte system is EC:PC:EMC:DMC=30%:5%:25%:20% (weight ratio), lithium salt 1 mol / L (0.5LiFSI+0.5LiPF6), and injection coefficient 3.1.
[0115] In the above steps, the positive electrode current collector uses an aluminum foil with a thickness of 12 μm, and the negative electrode current collector uses a copper foil with a thickness of 5 μm.
[0116] Example 2
[0117] The preparation method of the battery of Example 2 and the components and proportions of the positive and negative electrodes are the same as those of Example 1, except that the binder in Example 2 is only CF 4 The gas was plasma treated, but oxygen plasma was not used.
[0118] Example 3
[0119] The preparation method of the battery of Example 3 and the components and proportions of the positive and negative electrodes are the same as those of Example 1, except that the binder in Example 2 is not treated with oxygen plasma and CF 4 The gas is plasma treated.
[0120] Example 4
[0121] The preparation method of the battery and the components of the positive and negative electrodes of Example 4 are the same as those of Example 1, and the only difference is that the mass ratio of the components in the first coating and the second coating in Example 4 is different from that in Example 1.
[0122] The mass ratio of the components in the first coating layer of the positive electrode plate in Example 4 is LMFP: SP: CNT: PVDF (containing F group): dispersant: pore-forming agent = 97.79%: 0.5%: 0.4%: 0.96%: 0.2%: 0.15%; the mass ratio of the components in the second coating layer is LMFP: SP: CNT: PVDF (containing F group): dispersant: pore-forming agent = 96.21%: 0.5%: 0.4%: 2.24%: 0.2%: 0.45%.
[0123] Example 5
[0124] The preparation method of the battery and the components of the positive and negative electrodes of Example 5 are the same as those of Example 1, and the only difference is that the mass ratio of the components in the first coating and the second coating in Example 5 is different from that in Example 1.
[0125] The mass ratio of the components in the first coating layer of the positive electrode plate in Example 5 is LMFP: SP: CNT: PVDF (containing F group): dispersant: pore-forming agent = 97.45%: 0.5%: 0.4%: 1.20%: 0.2%: 0.25%; the mass ratio of the components in the second coating layer is LMFP: SP: CNT: PVDF (containing F group): dispersant: pore-forming agent = 95.35%: 0.5%: 0.4%: 2.80%: 0.2%: 0.75%.
[0126] Example 6
[0127] The preparation method of the battery and the ratio of the positive and negative electrode components of Example 6 are the same as those of Example 1. The only difference is that the dispersant in the positive electrode plate of Example 6 is different from that in Example 1. The dispersant in the positive electrode plate of Example 6 is polyacrylic acid (PAA).
[0128] 2. Battery performance test
[0129] (1) DCR test
[0130] Test method: fully charge the battery at 25℃, leave it for 0.5h, then fully discharge it, and record the discharge capacity Q. Fully charge the battery again, leave it for 0.5h, then discharge it at 0.1C for 0.5Q, leave it for 1h, record the voltage at this time as V0, then discharge it at 1C for 30s, record the voltage V1 and current I at the end of discharge, then DCR = (V0-V1) / I, in mΩ.
[0131] Full discharge means discharging to 2.5V at 1C at 25℃.
[0132] Full charge means charging at a constant current of 0.33C to the cut-off voltage (LFP3.65V, LMFP4.2V) at a temperature of 25°C, and then changing to constant voltage charging with a cut-off current of 0.05C.
[0133] The above-mentioned DCR test was performed on the batteries prepared in Examples 1 to 6, respectively. The test results are shown in Table 1.
[0134] (2) Cycle test
[0135] The batteries prepared in Examples 1 to 6 were subjected to full charge and discharge cycles at 25° C., and the capacity retention rate after 500 cycles was recorded. The test results are shown in Table 1.
[0136] Table 1
[0137] plan DCR / mΩ Capacity retention rate after 500 cycles / % Example 1 0.87 97.50 Example 2 0.93 96.40 Example 3 0.98 95.90 Example 4 1.01 95.60 Example 5 0.96 96.20 Example 6 1.05 94.20
[0138] From the data of Example 1, it can be seen that the battery of Example 1 has a lower internal resistance and a higher capacity retention rate, which proves that the battery of Example 1 has better dynamic performance and a higher cycle life. The reason is that in the positive electrode sheet of Example 1, PVDF is first treated with oxygen plasma and then treated with CF 4 The gas is plasma treated to form PVDF with an F group. Since the positive electrode active material layer of Example 1 adopts PVDF with an F group, the electron affinity and surface hydrophobicity of the binder are significantly improved, which can not only improve the hydrophobicity of the positive electrode sheet, but also reduce the internal resistance of the battery. Therefore, the kinetic performance and cycle life of the battery can be significantly improved.
[0139] Compared with Example 1, the internal resistance of the battery in Example 2 increases and the capacity retention rate decreases. The reason is that the PVDF in Example 2 only uses CF 4 The PVDF of Example 1 was treated with CF 4 Before the gas plasma treatment, PVDF was treated with oxygen plasma. The oxygen plasma treatment of PVDF can activate the surface of the binder, which is beneficial to the subsequent CF 4 During the gas plasma treatment, the attachment rate of the F group on the PVDF surface is increased, and the fluorine content is increased. Therefore, compared with Example 2, Example 1 can further reduce the internal resistance of the battery and improve the dynamic performance of the battery.
[0140] Compared with Example 1 and Example 2, the internal resistance of the battery in Example 3 increases and the capacity retention rate decreases. The reason is that the PVDF in Example 3 is not plasma treated and the surface does not contain the hydrophobic group F. Comparing the data of Example 3 with those of Example 1 and Example 2, it can be seen that when PVDF with the F group is used in the positive electrode sheet, the internal resistance of the battery can be effectively reduced, the capacity retention rate can be improved, and the dynamic performance and cycle life of the battery can be improved.
[0141] Compared with Example 1, the internal resistance of the batteries in Examples 4 and 5 increases, and the capacity retention rate decreases. The binder and pore-forming agent contents in Example 4 are lower, while the binder and pore-forming agent contents in Example 5 are higher. This proves that when the binder and pore-forming agent contents in the positive electrode sheet are too low or too high, the internal resistance of the battery increases, the capacity retention rate decreases, and the battery's kinetic performance and cycle life are affected.
[0142] Compared with Example 1, the internal resistance of the battery in Example 6 increases and the capacity retention rate decreases. In Example 6, the dispersant used is an ionic dispersant polyacrylic acid, while the dispersant used in Example 1 is a non-ionic dispersant. This proves that the use of a non-ionic dispersant in the positive electrode plate can reduce the internal resistance of the battery, improve the capacity retention rate, and thereby improve the battery's kinetic performance and cycle life.
[0143] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0144] The embodiments, implementation methods and related technical features of the present application can be combined and replaced with each other without conflict.
[0145] The above are only preferred embodiments of the present application and do not constitute any form of limitation to the present application. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.
Claims
1. A positive electrode sheet, characterized in that: It includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer includes at least one coating layer; The coating comprises a binder, wherein the binder comprises a first binder material and / or a second binder material; Wherein, at least one of the coatings includes the first bonding material, and the first bonding material has a hydrophobic group.
2. The positive electrode sheet according to claim 1, characterized in that: The positive electrode active material layer includes a first coating layer and a second coating layer, wherein the first coating layer is located on a side of the second coating layer away from the positive electrode current collector, the first coating layer includes the first binding material, and the second coating layer includes the first binding material or the second binding material.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The hydrophobic group contains fluorine.
4. The positive electrode sheet according to claim 1 or 2, characterized in that: The first bonding material is polyvinylidene fluoride having a hydrophobic group, and the second bonding material is polyvinylidene fluoride.
5. The positive electrode sheet according to claim 4, characterized in that: In the first bonding material, the hydrophobic group is a fluorine-containing group, and the fluorine-containing group is connected to the polyvinylidene fluoride through a chemical bond.
6. The positive electrode sheet according to claim 2, characterized in that: The coating also includes a pore former; The binder content in the first coating layer is less than or equal to the binder content in the second coating layer, and the pore former content in the first coating layer is less than or equal to the pore former content in the second coating layer.
7. The positive electrode sheet according to claim 6, characterized in that: The coating layer also includes a positive electrode active material, a conductive agent and a dispersant; The total mass ratio of the positive electrode active material, the conductive agent, the binder, the dispersant and the pore former in the positive electrode active material layer is a:b:c:d:e, wherein a+b+c+d+e=1; The mass ratio of the positive electrode active material, the conductive agent, the binder, the dispersant and the pore former in the first coating layer is (1-bc-0.6d-0.5e): b:c:0.6d:0.5e; The mass ratio of the positive electrode active material, the conductive agent, the binder, the dispersant and the pore former in the second coating layer is (1-bc-1.4d-1.5e): b:c:1.4d:1.5e.
8. The positive electrode sheet according to claim 7, characterized in that: The positive electrode active material includes lithium manganese iron phosphate.
9. The positive electrode sheet according to claim 7, characterized in that: The dispersant is a non-ionic dispersant.
10. The positive electrode sheet according to claim 7, characterized in that: In the positive electrode active material layer, the mass percentage of the positive electrode active material ranges from 95.5% to 97.5%, the mass percentage of the conductive agent ranges from 0.3% to 1.6%, the mass percentage of the binder ranges from 1.4% to 2.0%, the mass percentage of the dispersant ranges from 0.1% to 0.4%, and the mass percentage of the pore former ranges from 0.1% to 1.0%.
11. A method for preparing a positive electrode sheet, characterized in that: include: Mixing the positive electrode active material, the conductive agent, the dispersant and the pore-forming agent with a solvent to form a first mixed solution; Mixing a first bonding material with the first mixed liquid to form a second mixed liquid; Using the second mixed solution to form at least one coating on the positive electrode current collector to obtain a positive electrode sheet; Wherein, the first bonding material has a hydrophobic group.
12. The method for preparing a positive electrode sheet according to claim 11, characterized in that: The step of preparing the first bonding material comprises: The precursor of the first bonding material is subjected to plasma treatment using a fluorine-containing gas to obtain the first bonding material having a fluorine-containing group.
13. The method for preparing a positive electrode sheet according to claim 12, characterized in that: Before the step of plasma treating the precursor of the first bonding material with a fluorine-containing gas, the method further comprises: The precursor of the first bonding material is plasma treated with oxygen.
14. The method for preparing a positive electrode sheet according to any one of claims 11 to 13, characterized in that: The step of using the second mixed solution to form at least one coating on the positive electrode current collector comprises: Applying the second mixed solution onto the positive electrode current collector to form a second coating layer; The second mixed solution is applied to a side of the second coating layer away from the positive electrode current collector to form a first coating layer.
15. The method for preparing a positive electrode sheet according to any one of claims 11 to 13, characterized in that: The step of using the second mixed solution to form at least one coating on the positive electrode current collector comprises: Mixing a second bonding material with the first mixed solution to form a third mixed solution; Applying the third mixed solution onto the positive electrode current collector to form a second coating layer; The second mixed solution is applied to a side of the second coating layer away from the positive electrode current collector to form a first coating layer.
16. A battery, characterized in that: Comprising the positive electrode sheet as described in any one of claims 1 to 10.
Citation Information
Patent Citations
Preparation of ultra-hydrophobic polyvinylidene fluoride membrane and product thereof
CN101463140A
Fast chargeable lithium iron phosphate polymer lithium ion battery with ultra-high magnifications and manufacturing method thereof
CN101651236A
Lithium ion battery electrode sheet, preparation method thereof, and lithium ion battery
CN109167021A
All-solid lithium ion battery with porous gradient structure and preparation method thereof
CN110350238A
Positive pole piece and lithium ion battery
CN117374224A